The Impact of artificial intelligence-based mathematics learning innovations on personal ethics - Sulis Janu Hartati; Nabilla Calista Putri Susanto (Universitas Muhammadiyah Prof. DR. HAMKA, 2025)
Purpose: To investigate the ethical implications of AI-based innovations (specifically ChatGPT) on students' personal ethics in mathematics education, evaluated against Indonesia's National Education Goals and Pancasila values. Design/methodology/approach: A Systematic Literature Review (SLR) was conducted. Data from 21 relevant articles, sourced from Google Scholar via Publish or Perish, were selected using strict inclusion criteria for qualitative meta-synthesis. Findings: Significant contradictions exist between current ChatGPT implementations and Indonesia's character-building objectives. AI integration frequently prioritizes cognitive outcomes, risking the neglect of students' personal ethics, spiritual values, and moral integrity. Practical implications: Educators and policymakers must urgently establish robust ethical guidelines. Frameworks are needed to ensure AI cultivates academic integrity and moral responsibility, rather than merely automating cognitive tasks. Originality/value: This study uniquely evaluates the global AI phenomenon in mathematics education through the philosophical lens of Pancasila, bridging a crucial literature gap regarding advanced educational technology and regional ethical frameworks. Purpose: Penelitian ini bertujuan menginvestigasi implikasi etis inovasi pembelajaran berbasis Artificial Intelligence (AI), khususnya ChatGPT, terhadap etika pribadi siswa dalam pendidikan matematika, berdasarkan Tujuan Pendidikan Nasional Indonesia dan nilai Pancasila. Design/methodology/approach: Systematic Literature Review (SLR) dilakukan. Melalui perangkat lunak Publish or Perish dan basis data Google Scholar, 21 artikel relevan dipilih berdasarkan kriteria ketat untuk disintesis secara kualitatif. Findings: Terdapat kontradiksi substansial antara implementasi ChatGPT saat ini dengan tujuan pembentukan karakter nasional. Penggunaan AI sering memprioritaskan pencapaian kognitif, sehingga berpotensi mengabaikan etika pribadi, nilai spiritual, dan integritas moral siswa. Practical implications: Pendidik dan pembuat kebijakan mendesak perlu menetapkan pedoman etis yang kuat. Kerangka kerja praktis dibutuhkan agar teknologi AI mendidik nilai humanis dan tanggung jawab moral, bukan sekadar memfasilitasi jalan pintas akademis. Originality/value: Penelitian ini menawarkan kebaruan dengan mengevaluasi fenomena global AI dalam pendidikan matematika melalui perspektif filosofis lokal (Pancasila), mengisi kesenjangan literatur antara teknologi pendidikan mutakhir dan kerangka etika regional.